Validity of questionnaire self-reports on computer, mouse and keyboard usage during a four-week period. Issue 8 (26th March 2007) - Mikkelsen, Sigurd; Vilstrup, Imogen; Lassen, Christina Funch; Kryger, Ann Isabel; Thomsen, Jane Frølund; Andersen, Johan Hviid
Abstract : Objective: To examine the validity and potential biases in self-reports of computer, mouse and keyboard usage times, compared with objective recordings. Methods: A study population of 1211 people was asked in a questionnaire to estimate the average time they had worked with computer, mouse and keyboard during the past four working weeks. During the same period, a software program recorded these activities objectively. The study was part of a one-year follow-up study from 2000–1 of musculoskeletal outcomes among Danish computer workers. Results: Self-reports on computer, mouse and keyboard usage times were positively associated with objectively measured activity, but the validity was low. Self-reports explained only between a quarter and a third of the variance of objectively measured activity, and were even lower for one measure (keyboard time). Self-reports overestimated usage times. Overestimation was large at low levels and declined with increasing levels of objectively measured activity. Mouse usage time proportion was an exception with a near 1:1 relation. Variability in objectively measured activity, arm pain, gender and age influenced self-reports in a systematic way, but the effects were modest and sometimes in different directions. Conclusion: Self-reported durations of computer activities are positively associated with objective measures but they are quite inaccurate. Studies using self-reports to establish relations between computer work times and musculoskeletal pain could be biased and lead to falsely increased or decreased risk estimates.